Contribution to the Medieval Building Technology Based on the Reconstruction of a Rounded Church - Ákos Nemcsics (EXARC Journal)
This article presents the experimental archaeological project to build a medieval rotunda reconstruction using rough stone building technology. Here, a medieval rotunda reconstruction is presented by contemporary building technology. The rough stone building technology on an experimental archaeological project is demonstrated.